2014
DOI: 10.1088/0957-0233/25/3/035204
|View full text |Cite
|
Sign up to set email alerts
|

A linear relationship between the Hall carrier concentration and the effective absorption coefficient measured by means of photothermal radiometry in IR semi-transparent n-type CdMgSe mixed crystals

Abstract: In this work we demonstrate the ability to measure the effective infrared absorption coefficient in semiconductors by a photothermal infrared radiometry (PTR) experiment, and its correlation with the Hall carrier concentration. The amplitude and phase of the PTR signal were measured for Cd1−xMgxSe mixed crystals, with the magnesium content varying from x = 0 to x = 0.15. The PTR experiments were performed at room temperature in thermal reflection and transmission configurations using a mercury cadmium tellurid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…The main interest of our investigations is semiconductors of the A2B6 group. In this case, the lifetimes of generated carriers are short in comparison to silicon and for low frequencies of modulation, the carriers phenomena do not play a role as important as in the case of silicon or germanium [16,17].…”
Section: Since It Is Very Sensitive and Is Complementary Tomentioning
confidence: 94%
“…The main interest of our investigations is semiconductors of the A2B6 group. In this case, the lifetimes of generated carriers are short in comparison to silicon and for low frequencies of modulation, the carriers phenomena do not play a role as important as in the case of silicon or germanium [16,17].…”
Section: Since It Is Very Sensitive and Is Complementary Tomentioning
confidence: 94%
“…The effective IR absorption coefficient and the thermal diffusivity of CdSe crystals were estimated using the onedimensional heat transport model for IR semitransparent crystals [5]. The experimental procedure consists in measuring the PTR signal in the transmission and reflection configurations with the PTR signal obtained in reflection configuration used as the reference signal.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of semiconductors, PTR additionally yields information about the recombination parameters [3,4]. Recently, it was found that for infrared (IR) semitransparent semiconductors, it is possible to obtain information on the carrier concentration with quantitative values after calibration to Hall carrier concentration [5]. In this paper, a simple normalization procedure of the PTR spectra, which allows to determine the carrier concentration in CdSe single crystals using the normalized effective IR absorption coefficient measured by means of the PTR method and the theory proposed by Ruda [6], is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to investigate the thermal properties of Zn 1-x-y Be x Mn y Se mixed crystals as a function of Be and Mn contents. The thermal diffusivity can be obtained with various methods [9][10][11][12]. In this paper, the thermal diffusivity of the investigated materials is obtained with PPE technique [13][14][15] in the back detection configuration, coupled with the chopping frequency of the incident radiation scanning procedure.…”
Section: Introductionmentioning
confidence: 99%